2016
DOI: 10.2519/jospt.2016.5824
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Second Metatarsophalangeal Joint Instability in a Professional Dancer: A Case Report

Abstract: Therapy, level 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Moreover, two subjects in particular showed VISA-A scores of ≥90 points, demonstrating that they had recovered from Achilles tendinopathy. In addition, McConnell et al (2016) also reported clinically significant changes in the functional test results of patients with Achilles tendinopathy after applying IASTM. Furthermore, a study by McCormack et al (2016) showed that applying a combination of eccentric exercise together with IASTM for 12 weeks resulted in a greater improvement in VISA-A scores of patients with Achilles tendinopathy when compared with applying eccentric exercise alone.…”
Section: Instrument-assisted Soft Tissue Mobilizationmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, two subjects in particular showed VISA-A scores of ≥90 points, demonstrating that they had recovered from Achilles tendinopathy. In addition, McConnell et al (2016) also reported clinically significant changes in the functional test results of patients with Achilles tendinopathy after applying IASTM. Furthermore, a study by McCormack et al (2016) showed that applying a combination of eccentric exercise together with IASTM for 12 weeks resulted in a greater improvement in VISA-A scores of patients with Achilles tendinopathy when compared with applying eccentric exercise alone.…”
Section: Instrument-assisted Soft Tissue Mobilizationmentioning
confidence: 86%
“…Recently, McConnell et al (2016) applied eight sessions of IASTM over a 4-week period in adults with Achilles tendinopathy and found that Young’s modulus, a measure of elasticity, increased by 34.5% and stiffness increased by 31.8%, while the Victorian Institute of Sport Assessment for Achilles (VISA-A) score, an index showing the severity of Achilles tendinopathy, improved from an average of 13 points to 86 points. Moreover, two subjects in particular showed VISA-A scores of ≥90 points, demonstrating that they had recovered from Achilles tendinopathy.…”
Section: Instrument-assisted Soft Tissue Mobilizationmentioning
confidence: 99%
“…Chronic physical stressors associated with lesser MTP instability include high heels, 5,27,30,38 a relatively long second metatarsal known as Morton’s toe, 9,13,29,31,37 and hallux valgus. 13,37 Additionally, in aged individuals, fat pad atrophy makes the joint more vulnerable.…”
Section: Etiology Of Lesser Mtp Instabilitymentioning
confidence: 99%
“…2,27,32 Cases occur in both acute and chronic settings across many sports. 5,7,17,29,37 Unfortunately, diagnosis is frequently delayed or missed altogether, leading to progressive instability that may require surgery. 5,17,22,37,40…”
mentioning
confidence: 99%
“…Bronner et al [10] developed a self-administered questionnaire called the Dance Functional Outcome Survey (DFOS), to assess healthy state and symptom severity in injured dancers. The DFOS has been used to assess recovery following rehabilitation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%